2021
DOI: 10.1177/08861099211068241
|View full text |Cite
|
Sign up to set email alerts
|

Examining Social Work Students Knowledge of and Attitudes About Abortion and Curriculum Coverage in Social Work Education

Abstract: Despite social work's stated commitment to abortion rights, research on this topic is not prolific within the discipline (Begun et al., 2016). If we are to live up to our ethical principles, this should be changed. The authors posit that increasing students’ exposure to and understanding of abortion is necessary in the preparation of competent social work practitioners. Using Begun et al.’s (2016) Social Workers’ Abortion Attitudes, Knowledge, and Training questionnaire, the authors expanded the survey by crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Linked to this, the need has also emerged to adequately train family counselling personnel, including social workers, as reported by Elena. This aspect has been underlined by other studies in literature as well, which have indicated that there are still gaps in this field, an aspect that contributes also to shape the way operators respond to women' s choices, since those who https://doi.org/10.14198/ALTERN.21262 Ines Testoni, Giulia Salvalaio, Sara Pompele y Adriano Zamperini are better informed tend to present a more pro-choice attitude (Witt et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Linked to this, the need has also emerged to adequately train family counselling personnel, including social workers, as reported by Elena. This aspect has been underlined by other studies in literature as well, which have indicated that there are still gaps in this field, an aspect that contributes also to shape the way operators respond to women' s choices, since those who https://doi.org/10.14198/ALTERN.21262 Ines Testoni, Giulia Salvalaio, Sara Pompele y Adriano Zamperini are better informed tend to present a more pro-choice attitude (Witt et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…As concerns instead the reasons that can bring a woman to this decision, they can be linked to intense economic difficulties, unbalanced relationship dynamics with the partner or one' s family, young or elder age, the pregnancy as a result of abuse, or the fact that the woman is not psychologically ready to deal with maternity (Littman, Zarcadoolas, & Jacobset, 2009). Linked to this, there may also be conditions of poor information regarding sex education and contraception (Caruso, 2020a;Guida et al, 2019), many times even among socio-sanitary personnel who supports women in these aspects (Mauri & Squillace, 2017;Witt, Younes, Goldblatt Hyatt, & Franklin, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…• Teach and promote feminist social work again. It has slipped off the curriculum so easily over the last 20 years, as social work education has been besieged by the neoliberal drive to focus on investigation and risk assessment (see Witt et al, 2021;Younes et al, 2021). • Centre a feminist perspective in thinking about the women we work with in the profession, 'moving away from seeing women as merely the object of the social work gaze, the focus of scrutiny and judgment' (Beddoe, 2021: 9).…”
Section: Introduction (Crsw Editor-in-chief Michael Lavalette Uk)mentioning
confidence: 99%
“…Disturbingly, current legislation attempts to recruit academics into these efforts. As Witt et al (2022) described in the pages of Affilia , Idaho and Missouri both have laws that impinge on academic freedom by restricting the information faculty can offer students, such that faculty are not allowed to provide information that could be interpreted as “promoting” abortion.…”
mentioning
confidence: 99%